Relating Instructor Feedback and Student Reception in the Clinical Environment. - Nolan, Tanya; Loubier, Cynthia (Radiologic Technology)
Purpose To identify the relationship between instructor feedback and student receptivity to it in a clinical setting. Methods Using a correlational design with a convenience sample of 132 students enrolled in radiologic science programs, the authors conducted an electronic survey that included a demographic section, the Feedback Environment Scale (FES), and the Feedback Orientation Scale (FOS). The first research question was whether a relationship existed between the aggregate predictor FES and criterion FOS variables. The second research question was whether relationships existed between separate FES variables and FOS variables. Responses were categorized as interval or ratio data and transferred to the statistical package for the social sciences software for analysis. Statistical Pearson r, coefficients of determination, and regression analysis were used to identify the significance and direction of the correlations. Results A significant (P = .01) positive relationship (r = .50) was found between aggregate FES and FOS variables, and the null hypothesis was rejected. Significant (P = .01) correlations were found between the aggregate FOS and predictor FES variables of feedback quality (r = .51) and feedback delivery (r = .25). In addition, a significant (P = .01) correlation was identified between the aggregate FES value and the FOS variable self-efficacy (r = .50). The null hypothesis was not rejected for all correlations calculated between separate predictor (FES) and criterion (FOS) variables. Discussion Variables that positively influence the feedback exchange between clinical instructors and students are critical to identify and enhance. With detailed understanding of these variables and how they relate to one another, specific guidance can be fashioned to target common barriers affecting productive instructor feedback and student receptivity. Conclusion Clinical instructors are essential to the feedback environment and play a significant role in helping students receive, accept, and develop competency Feedback receptivity is promoted when students perceive consistent, relevant, specific, and altruistic messages. Training for clinical instructors should focus on principles of feedback quality and delivery to enhance the clinical instructor-student relationship and learning.